Amin Al-Khouli's Views on The Two Branches of Balaghah: Logical and Literature - Mohammad Izdiyan Muttaqin (UIN Siber Syekh Nurjati Cirebon, Indonesia, 2024)
Purpose: This research aimed to analyze Amin Al-Khouli's ideas in distinguishing between the two schools of Balaghah: the literary school and the logical school. Design/Methods/Approach: The research employs a qualitative approach, focusing on several key methods of analysis. Content analysis was conducted, examining both primary and secondary texts. The primary texts include Amin Al-Khouli's writings and publications on Balaghah. The main method of data collection for this research is document analysis, which involves collecting and analyzing a wide range of texts authored by Amin Al-Khouli, including his books